Análisis de rentabilidad y proyección financiera en ovinos pelibuey alimentados con ensilaje de maíz e inclusión de efluentes de elaeis guineensis - Triviño Zambrano, Carlos Xavier (2024)
The study focused on analyzing the profitability and financial projection of feeding Pelibuey sheep with corn silage and inclusion of African palm (Elaeis guineensis) effluents. It was proposed that supplementation with these agricultural byproducts could improve the profitability of sheep production, compared to the use of commercial feeds. The general objective was to analyze the profitability and financial projection in Pelibuey sheep fed with corn silage and inclusion of Elaeis guineensis effluents. The research was carried out at the Universidad Técnica Estatal de Quevedo, it had an experimental-descriptive approach. Different feeding treatments were evaluated with different levels of inclusion of corn silage and palm effluents. Economic variables such as fixed costs, variable costs, income, profitability, break-even point, net present value (NPV) and internal rate of return (IRR) were analyzed. The results show that feeding corn silage and palm effluent to sheep improved the profitability of treatment 1 compared to other treatments. The balance point was 162.83 kg. The 5-year financial analysis indicates that the best treatment has a positive NPV and an IRR higher than the discount rate, which makes it viable. Furthermore, the sensitivity analysis revealed that the project is robust to changes in key variables. Supplementation of Pelibuey sheep with corn silage and inclusion of African palm effluents improved the profitability of production. Long-term financial analysis demonstrates the viability of the best treatment, which is also resilient to possible variations in key factors.